Empowering Young Minds:: The Role of Interactive Media in Early Childhood Education - Asmara, Berda; Rihlah, Jauharotur; Rulyansah, Afib (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Learning evaluation is one of the essential elements in the education process aimed at measuring student’scompetency achievements. This study focuses on analyzing the objects of learning evaluation, covering cognitive, affective, and psychomotor aspects. A descriptive approach is used to illustrate the types of evaluation objects applied across various educational levels and their effectiveness in improving the quality of learning. Data were collected through literature studies, observations, and interviews with educators at the elementary to higher education levels. The findings indicate that the success of an evaluation heavily depends on the alignment of the evaluated objects with learning objectives and the evaluation methods employed. This study recommends the development of more innovative and inclusive evaluation strategies to support optimal learning processes.